The digital dilemma: analyzing the psychological impact of fear of missing out (FoMO) among university students in Cirebon - Novianti, Herny; Yusuf, Syamsu (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
This study explores the psychological and cultural dimensions of Fear of Missing Out (FoMO) among university students in Cirebon, Indonesia. Triggered by the rapid rise in social media engagement, FoMO has become a prevalent issue affecting students’ emotional well-being, academic focus, and self-regulation. Adopting a mixed-methods sequential explanatory design, the research involved a survey of 300 students from IAIN Syekh Nurjati and UNTAG Cirebon, followed by in-depth interviews with 30 selected participants. Quantitative data were analyzed using Structural Equation Modeling (SEM). Qualitative findings highlighted the influence of local collectivist culture in reinforcing FoMO, with students expressing emotional pressure to maintain online visibility for social belonging. A short-term self-management intervention conducted with 20 students showed a significant reduction in FoMO behaviors, indicating the potential effectiveness of digital wellness strategies. This study emphasizes the need for culturally sensitive approaches in addressing FoMO through emotional training, peer support, and digital self-regulation programs within university settings.